(untitled) (El-Wahat Journal for Research and Studies, 2021)
This Study Is Concerned With The Guarantees Approved By The Algerian Legislature To Protect The Right To Life To The Foetus And To Prevent Abuses Against Them In The Different Stages Of Its Development Through The New Health Act N° 18/11, With The Increasing Of Doctrinal Debate About The Need For Restrictive Abortion Acts. Most Legislations Have Legalized The Therapeutic Abortion, To Save The Pregnant Mother’s Life, It Has Been Found That The Algerian Legislator Considered That The Origin Is To Preserve The Pregnant Women’s Health And Providing The Necessary Medical Assistance. However, If The Mother’s Health Is In Danger, Therapeutic Abortion May Be Performed As A Necessary Medical Service To Avoid Serious And Permanent Harm. For This Reason, It Is Subject To Certain Conditions Aimed At Getting It Out Of The Dangerous To The Official Public Framework, Without Regulating The Abortion Of Pregnancy Resulting From Adultery, Rape And Deformed Foetus Key Words- Foetus, Abortion, Health Law, Necessary, Right To Life